The minor house dust mite allergen Der p 13 is a fatty acid‐binding protein and an activator of a TLR2‐mediated innate immune response. Issue 10 (29th April 2016) - Satitsuksanoa, P.; Kennedy, M.; Gilis, D.; Le Mignon, M.; Suratannon, N.; Soh, W. T.; Wongpiyabovorn, J.; Chatchatee, P.; Vangveravong, M.; Rerkpattanapipat, T.; Sangasapaviliya, A.; Piboonpocanun, S.; et al.
Abstract: Background: The house dust mite (HDM ) allergen Der p 13 could be a lipid‐binding protein able to activate key innate signaling pathways in the initiation of the allergic response. We investigated the IgE reactivity of recombinant Der p 13 (rDer p 13), its lipid‐binding activities, and its capacity to stimulate airway epithelium cells. Methods: Purified rDer p 13 was characterized by mass spectrometry, circular dichroism, fluorescence‐based lipid‐binding assays, and in silico structural prediction. IgE‐binding activity and allergenic potential of Der p 13 were examined by ELISA, basophil degranulation assays, and in vitro airway epithelial cell activation assays. Results: Protein modeling and biophysical analysis indicated that Der p 13 adopts a β‐barrel structure with a predominately apolar pocket representing a potential binding site for hydrophobic ligands. Fluorescent lipid‐binding assays confirmed that the protein is highly selective for ligands and that it binds a fatty acid with a dissociation constant typical of lipid transporter proteins. The low IgE‐binding frequency (7%, n = 224) in Thai HDM‐allergic patients as well as the limited propensity to activate basophil degranulation classifies Der p 13 as a minor HDM allergen. Nevertheless, the protein with its presumptively associated lipid(s) triggered the production of IL‐8 and GM‐CSF in respiratory epithelial cells through a TLR2‐, MyD88‐, NF‐kB‐, and MAPK‐dependent signaling pathway. Conclusions: Although a minor allergen, Der p 13 may, through its lipid‐binding capacity, play a role in the initiation of the HDM‐allergic response through TLR2 activation.